2017
DOI: 10.1021/acs.chemmater.7b01358
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of SiCxNy Using Si2Cl6 and CH3NH2 Plasma

Abstract: We developed a novel process for the atomic layer deposition (ALD) of SiC x N y films using a Si 2 Cl 6 and a CH 3 NH 2 plasma. Under self-limiting growth conditions, this ALD process led to SiC x N y films with up to 9 atomic percent carbon with a conformality >95% in 5:1 aspect ratio nanostructures. The surface reactions during ALD, and in particular the carbon incorporation mechanism, were studied using in situ attenuated total reflection Fourier transform infrared spectroscopy. Similar to the Si 2 Cl 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…On the other hand, PEALD has been used successfully to grow SiC x O y and SiC x N y films [111][112][113][114]. Ovanesyan et al developed a novel process for the ALD of SiC x N y films using a Si 2 Cl 6 and a CH 3 NH 2 plasma.…”
Section: Plasma-enhanced Atomic Layer Depositionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, PEALD has been used successfully to grow SiC x O y and SiC x N y films [111][112][113][114]. Ovanesyan et al developed a novel process for the ALD of SiC x N y films using a Si 2 Cl 6 and a CH 3 NH 2 plasma.…”
Section: Plasma-enhanced Atomic Layer Depositionmentioning
confidence: 99%
“…Ovanesyan et al developed a novel process for the ALD of SiC x N y films using a Si 2 Cl 6 and a CH 3 NH 2 plasma. They reported that under self-limiting growth conditions, this ALD process led to SiC x N y films with up to nine atomic percent carbon with a conformality > 95% in 5:1 aspect ratio nanostructures [113]. In recent work, Y.-L. Hsu reported on the deposition of SiC x N y films on the aluminum (Al) substrates using PEALD method and 1,3,5-Trimethyl-1,3,5-trivinylcyclotrisilazane (C 9 H 21 N 3 Si 3 , VSZ) single-source precursor in order to construct SiC x N y -based resistive switching memory [114].…”
Section: Plasma-enhanced Atomic Layer Depositionmentioning
confidence: 99%
See 3 more Smart Citations